Peculiarities of the Accumulation of Mineral Elements and Nitrogen in the Assimilation Apparatus of Scots Pine - Pavel A. Feklistov; Olga N. Tyukavina; Nataliya R. Sungurova; Sergey S. Makarov; Ivan N. Bolotov; Sergey N. Tarkhanov (Lesnoy Zhurnal (Forestry Journal), 2024)
The research has been carried out in the Arkhangelsk forestry of the Arkhangelsk Region in a drained shrub-sphagnum pine forest. Census trees of medium diameter and height for the stand have been selected, from which samples of needles, both living and dying yellow ones, and shoots of different ages have been taken on model branches. Soil samples have also been taken from the 3 upper horizons. It has been established that most of all nitrogen and mineral elements accumulate in the living needles – 4.4 % on average, in the dying needles and shoots there are 37–40 % less. Among all the elements, nitrogen, potassium and calcium make up the largest proportion; while the rest of the chemical elements are several time less. In descending order of the share, they are arranged in the following sequence: magnesium, sulfur, phosphorus, manganese, silicon, iron and aluminum. The most important mineral elements are derived in significant quantities from the dying yellow needles. The content of sulfur, magnesium, phosphorus, manganese and iron decreases in them by 3.3, 2.1, 8.0, 1.5 and 1.4 times, respectively, compared to the living needles. Data on the presence of nitrogen and mineral elements in the soil horizons A0, T1 and T2 have been obtained. It has been established that some of the essential elements for the life of a tree are concentrated in the living needles in much larger quantities than in the soil: potassium, phosphorus, manganese and calcium – by 12.0, 4.0, 6.0 and 1.9, respectively. The yellow falling needles create a biological cycle of substances. The amount of nitrogen and ash constituents in these needles is proportional to their presence in the soil. In turn, the content of mineral elements in the shoots is close to their amount in the yellow falling needles, on the one hand, and on the other, depends on the age of the shoots. There is a steady trend of decreasing the content of nitrogen, potassium, phosphorus and sulfur with the age of the shoots.